Integrating clinical pharmacists within general practice: protocol for a pilot cluster randomised controlled trial - Croke, Aisling (BMJ Open, 2021)
INTRODUCTION: Managing patients with multiple conditions (multimorbidity) is a major challenge for healthcare systems internationally, particularly in older patients. Multimorbidity and subsequent polypharmacy increase treatment burden and the risk of potentially inappropriate prescribing, and both are complex to manage in primary care. Limited evidence suggests integration of pharmacists into general practice teams could improve medication management for patients with multimorbidity and polypharmacy. Building on findings from a non-randomised, uncontrolled General Practice Pharmacist (GPP) feasibility study conducted in Irish primary care, the aim of this study is to conduct a pilot cluster randomised controlled trial (cRCT) of the GPP study, to assess feasibility, intervention impact, costs and appropriateness of continuing to a definitive cRCT. METHODS AND ANALYSIS: This pilot cRCT will involve 8 general practitioner (GP) practices and 120 patients. Practices will identify and recruit patients aged ≥65 years, who are taking ≥10 regular medications. Practices will be allocated to intervention or control after baseline data collection. Intervention practices will have a pharmacist integrated within their service, working with GPs, patients and practice staff to optimise prescribing and other medication-related activities. Control practices will provide standard GP care. The primary feasibility outcomes will include recruitment rate, uptake of medication reviews and study retention. For the primary clinical outcome, the number of potentially inappropriate prescribing incidences per patient will be collected. Secondary outcomes will include medication-related outcomes, patient-reported outcome measures, and data pertaining to the role and impact of the pharmacist on prescribing. In addition, economic and process evaluations will be conducted. ETHICS AND DISSEMINATION: This trial has been approved by the Irish College of General Practitioners Research Ethics Committee and will be performed in accordance with the Declaration of Helsinki. The results will be reported in peer-reviewed journals and be presented at national and international conferences. TRIAL REGISTRATION NUMBER: ISRCTN Registry (https://doi.org/10.1186/ISRCTN18752158).